PENERAPAN TEORI CONNECTIONISM DALAM PEMBELAJARAN SUSUN HURUF SISWA MI DARUSSALAM GRESIK - Umi Latifah (Universitas Islam Malang, 2021)
Abstract: This research is motivated by children becoming the spirit of learning in various creative ways given by teachers or parents to children. Many ways and theories in learning exist to increase the spirit of children in the learning process, one of which is the theory of connectionism. Because it takes stimulus to train the development of the child in order to produce a response that is in accordance with the stimulus provided by practicing and appreciating the child's results. This article limits the problem to the application of connectionism theory with the law contained in the theory, namely the law of readiness, the law of practice, and the law of consequence. This study uses a qualitative approach. The design of this research is descriptive. This research data was obtained by conducting observations of learning activities of MI Darussalam Gresik students. The population of this study is junior high school students. The sample of this study is a grade 1 student of MI Darussalam Gresik. The data collection techniques used are descriptive. Based on the observations of learning obtained, 1)the law of readiness of STUDENTS MI Darussalam Gresik, 2)the law of training students MI Darussalam Gresik, and 3) the law due to students MI Darussalam GresikKeywords: learning, connectionism, lettering